Mangiferin ameliorates polycystic ovary syndrome in rats by modulating insulin resistance, gut microbiota, and ovarian cell apoptosis - Yong, Zhang; Mimi, Chen; Yingjie, Li; Yichen, Guo; Yansu, Yu; Zhi, Zhou; Hui, Lu; Si, Yao; Chongming, Wu; Xiaopo, Zhang; Ning, Ma; Weiying, Lu (Frontiers in Pharmacology, 2024)
Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disorder characterized by hyperandrogenism, prolonged anovulation and polycystic ovaries. However, there are no effective interventions to treat this disorder. As previously shown, mangiferin modulated the AMPK and NLRP3 signal pathways to alleviate nonalcoholic fatty liver disease (NAFLD). In recent years, mangiferin has emerged as a promising drug candidate for treating metabolic diseases. In this study, we aim to investigate the effects and mechanisms of mangiferin in PCOS rats induced by letrozole (LET) combined with a high-fat diet (HFD). The efficacy of mangiferin in PCOS rats was evaluated through estrous cycle detection, serum/tissue biochemical analysis, and hematoxylin and eosin (HE) staining of ovarian tissue. The mechanisms of mangiferin's effects on PCOS rats were analyzed using 16S rRNA sequencing, RNA-seq, western blotting (WB), and immunohistochemical (IHC) staining. Our results displayed that mangiferin showed a promising effect in PCOS rats. It improved lipid metabolism, glucose tolerance, insulin resistance, hormonal imbalance, ovarian dysfunction, and adipocyte abnormalities. RNA-seq analysis indicated that mangiferin may be involved in several signal pathways, including apoptosis, necrosis, and inflammation. Furthermore, western blot and immunohistochemical staining demonstrated that mangiferin regulates Caspase-3 and Cytc, exhibiting anti-apoptotic activity in the ovaries. Additionally, mangiferin significantly altered the gut microbiota community of PCOS rats, changing the abundance of firmicutes, bacteroidota, proteobacteria, and actinobacteria at the phylum level and the abundance of Blautia, Coprococcus, Roseburia, and Pseudomonas at the genus level. In conclusion, mangiferin is a promising and novel therapeutic agent for PCOS as it ameliorates insulin resistance, gut microbiota and ovarian cell apoptosis.